A Very Unusual Accidental Mechanical Asphyxia of Choking with a Whole Solea Solea. Issue 2 (6th December 2016) - Busardò, Francesco Paolo; Mannocchi, Giulio; Pugnetti, Paola; Santurro, Alessandro; Maggiordomo, Aldo; Zaami, Simona
Abstract: The case here reported involves a schizophrenic 19‐year‐old girl under treatment with clotiapine, which was well tolerated except for a moderate dry mouth. The woman ingested a whole sole ( Solea solea ), which caused a very rapid death by choking. A complete autopsy was performed 24 h later, as well as histological and toxicological analysis. At autopsy, the sole was wedged in the esophagus causing a choking ab extrinseco. The fish had a length of 18 cm and a maximum width of 6 cm, weighing 188.7 g. Toxicological analysis detected 0.57 mg/L of clotiapine in blood, which falls within the therapeutic range. The peculiarity of this case is represented by two factors: one is the choking by fish and the second was the adverse affect caused by clotiapine, which induced a condition of dry mouth making the act of swallowing even more difficult, thereby contributing to a very rapid mechanical asphyxia and the death of the young woman.